PENGARUH PEMBAYARAN NON TUNAI (E-WALLET) TERHADAP PERILAKU KONSUMTIF MAHASISWA JURUSAN PENDIDIKAN ILMU SOSIAL FKIP UNIVERSITAS MULAWARMAN - Patrisia, Patrisia; Ellyawati, Noor; Piar, Christie Stephanie; Reza, Reza; Astuti, Ratna Fitri (UNIVERSITAS MUHAMMADIYAH METRO, 2023)
The purpose of this research is to find out: 1) the usage of e-wallet for studentsmajoring in PIPS and FKIP at Mulawarman University. 2) Consumptive behaviorof students majoring in PIPS/FKIP at Mulawarman University 3) the effect of ewallet on the consumption behavior of students majoring in PIPS FKIP atMulawarman University. This study uses a quantitative approach. The populationin this study is a Social Science Education student at Mulawarman University, Classof 2018, with a sample of 65 respondents. Researchers gathered information bydistributing questionnaires with Likert scale measurements and conductinginterviews with Mulawarman University's 2018 Social Science Class.The results ofthis study show that an e-wallet produces a regression coefficient of 3.808, meaningthat e-wallets have an effect on consumptive behavior. In conclusion, this studyreveals:1) The most widely used type of e-wallet is ShopeePay. 2)The level ofconsumption among students is still reasonable because students consider thebenefits and uses of the product. 3) The use of e-wallets that influence consumptivebehaviour i.e. discount. 4) Some indicators have no effect on behavior becausestudents still see the benefits of these products. Besides that, not all products makestudents consume directly excessive amounts of them.